SOME PROBLEMS OF SYSTEMATISING LEGAL MEANS TO ENSURE THE DEVELOPMENT OF A TERRITORY (ON THE EXAMPLE OF GEOPARKS) - VOLKOV Gennadiy Alexandrovich (Правовое государство: теория и практика)
The legislation on specially protected natural areas is currently being reformed to ensure tourism development. New territories emerge, within the boundaries of which, on the one hand, there are unique natural sites, including geological ones, corresponding to the criteria of specially protected natural areas, and on the other hand, these areas are not given a special protection regime and they intersect with the previously established specially protected natural areas. This raises concerns about the proper preservation of unique natural sites and necessitates the definition of a set of legal means that could ensure both the economic development of such territories (primarily active tourism) and the preservation of natural sites of special scientific, cultural and aesthetic value, that means sustainable development of territories. Based on the intersectoral, instrumental and formal-legal approach, the article considers theoretical foundations of the legal regime of specially protected natural areas (option – to give this regime to geoparks) for the purposes of ensuring and preserving unique geological sites and economic development of the territory, including tourism; alternative legal means of ensuring these purposes, including legal institutions for territory planning and integrated territorial development; advantages and disadvantages of the considered options for the application of these legal means. The article proposes a system of legal means and legislative changes for the development of geoparks.